Finance and Development, March 2015. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2015)
This chapter discusses the impact of global recession on the working population and looks at the future of work in the global economy from a variety of angles. IMF economist Prakash Loungani leads off with an overview of the global jobs landscape and examines the reasons behind the slow recovery of jobs in the wake of the global financial crisis. The chapter also highlights an argument for a jobs- and wage-led global recovery, while IMF researchers probe the relationship between declining trade union membership and inequality.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet